PENDIDIKAN KARAKTER MELALUI COMPREHENSIVE PROJECT PADA SISWA KELAS IV SEKOLAH CERDAS PEKANBARU - Mistia Wati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the awareness of the importance of character education through a comprehensive project that has not been implemented properly. What's more known, the condition of Indonesian human character today seems to experience chronic disorientation. The research method used is a qualitative descriptive research method that aims to collect data on character education through a comprehensive project on fourth grade students of Sekolah Cerdas Pekanbaru. The subjects of this study were 1 homeroom teacher, 1 person in charge of the school, and 5 students. The data collected from this study is the first to determine the data source, make observations, then do documentation for further clarification by conducting interviews with data sources. The results of the study are that character education through a comprehensive project has been carried out in accordance with its programs even though it has not fulfilled all observational indicators. Based on the results of these studies, it can be concluded that it has been implemented but has not been implemented in its entirety, because not all characters that have been fulfilled as an indicator are also marked character education given through a comprehensive project has not been internalized as a whole and has not become a daily habit for fourth grade students.